Interruption of the visual cycle in a novel animal model induces progressive vision loss resembling Stargardts Disease - Fabiana Sassone; Catherine Estay-Ahumada; Michel J. Roux; Dominique Ciocca; Paola Rossolillo; Marie-Christine Birling; Janet R. Sparrow; Diego Montenegro; David Hicks (Scientific Reports)
Abstract Mutations in the gene ABCA4 coding for photoreceptor-specific ATP-binding cassette subfamily A member 4, are responsible for Stargardts Disease type 1 (STGD1), the most common form of inherited macular degeneration. STGD1 typically declares early in life and leads to severe visual handicap. Abca4 gene-deletion mouse models of STGD1 accumulate lipofuscin, a hallmark of the disease, but unlike the human disease show no or only moderate structural changes and no functional decline. The human macula is highly enriched in cones, and reasoning that the low cone percentage in mice retinas (< 3%) might compromise faithful modelling of human maculopathies, we performed sub-retinal injections of CRISPR/Cas9-abca4 Adeno-Associated Virus constructs into young Sand Rats (Psammomys obesus), a diurnal rodent containing > 30% cones. Compared to control injections of AAV-abca4-GFP, treated eyes exhibited extensive retinal degeneration by two months. Sanger sequencing of the CRISPR targeted sequence show a clear edition of Abca4 gene. Non-invasive fundus imaging showed widespread photoreceptor loss, confirmed by ocular coherence tomography. Functional recording by single flash and flicker electroretinography showed significant decline in photopic (cone) light responses. Post-mortem real-time PCR, immunohistochemistry and western blotting showed significant decrease of cone-specific (MW cone opsin) but not rod-specific (rhodopsin) markers. Transmission electron microscopy showed large numbers of lipid inclusions in treated but not control retinal pigmented epithelium. Finally, ultra-high performance liquid chromatography analysis of whole P. obesus eyes showed the presence of all-trans retinal-dimer, not detected in rod-rich rat eyes. In conclusion, Abca4 knockout in P. obesus results in a predominantly cone degeneration phenotype, more accurately reflecting the etiology of human STGD1, and should be valuable for characterizing pathogenic pathways and exploring treatment options.